A review of thermal, microstructural and constitutive modelling of 9Cr steel for power plant applications: Towards a through-process model for structural integrity of welded connections. (February 2020) - Ardghail, P. Mac; Leen, S.B.; Harrison, N.M.
Abstract: Life prediction for 9Cr steel welded components is an important issue facing power plant as it moves from steady-state, base-load operation to transient, flexible operation. Welding and heat-treatment of 9Cr components alters the steel microstructure to produce a heat-affected zone, which is susceptible to early failure under creep and high-temperature cyclic conditions. Optimal welding and heat treatment processes cannot feasibly be identified experimentally but finite element simulation is a practical solution to this problem. A review of modelling methodologies for welding, heat treatment and in-service operation in thermal power plant for 9Cr steel is presented here. The authors consider that macro-scale, physically-based models are the most promising models currently available since they account for changes in material microstructure while still being practical for simulations involving component-sized FE geometries. Highlights: Description given of 9Cr steel microstructure, welding processes. Description given of 9Cr steel welding thermal modelling methods. Description given of 9Cr steel microstructure evolution modelling methods. Description given of 9Cr steel constitutive modelling methods. Sample results of residual stress predictions shown, life-prediction methods described.